Pengaruh Karakteristik Individu dan Lingkungan Kerja terhadap Kinerja Pegawai dengan Modal Sosial sebagai Variabel Moderasi - Laan, Rahmat (Patria Artha University, 2018)
This study aims to (1) determine the influence of individual characteristics and workenvironment partially and simultaneously on the performance of kelurahan employee inMaulafa sub-district, (2) to know the influence of individual characteristic to theperformance of kelurahan employee in Maulafa sub-district with social capital asmoderation variable, (3) mengatahui the influence of work environment on theperformance of kelurahan employees in the district Maulafa with social capital as amoderation variable. The sample of 66 employees in 9 sub-districts in Maulafa subdistrictwas determined by proportional random technique. Data were analyzed bymultiple regression models and residual approach model. The result of the researchshows that (1) the individual characteristic and work environment either partially orsimultaneously have a significant effect on the performance of outgoing employees inMaulafa sub-district, (2) individual characteristics have no significant effect on employeeperformance moderated by social capital, (3) have a significant effect on employeeperformance which is moderated by social capital.